(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study deals with the application the dimensions of the pioneer organization, which included: (creative career, pioneering employee, entrepreneurial culture, flexible organizational structure), and its impact on environmental protection from pollution. The research sought to achieve a set of objectives, including the possibility of diagnosing the role played by the pioneer organization in preserving the environment and protecting it from pollution, and the research problem started with the company in question, which gave great importance to the dimensions of pioneering and its application in its work and raising the possibilities and capabilities available to achieve the pioneering dimensions. The research community consisted of (30) individuals, the questionnaire was used as a tool for collecting statistical data that was analyzed using the statistical program (SPSS). The research was based on a set of hypotheses to study the effect of the dimensions of the independent variable (the dimensions of the pioneering organization) on the dependent variable (pollution). The research was based on a descriptive statistics method (arithmetic mean, standard deviation ...); the research reached a number of conclusions: The existence of a relationship between the two variables, the dimensions of the pioneering organization and the entrepreneurial environment in the company. High level of interest of the company in the dimensions of the pioneering organization in the company. The researchers recommended a set of recommendations, including the need to give great attention to the application of the dimensions of the pioneering organization, to its impact in protecting the working environment from pollution.